Enhancement of Students’ Argumentation Skills based on The Implementation of Argument Driven Inquiry Learning Model - Ummi Lailatul Azizah; Badrut Tamam; Mochammad Ahied; Nur Qomaria; Wiwin Puspita Hadi (Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Jember, 2022)
Abstract This research was conducted because there are still many junior high school students who have lowargumentation skills so the purpose of this study is to improve students' argumentation skills with theArgument Driven Inquiry (ADI) learning model. The research method was included in the Pre-experimentwith One Group Pretest-posttest Design which was carried out at Al-Hamidiyah Blega Junior High Schoolfor the 2021/2022 Academic Year. Data collection techniques are carried out through tests, questionnaires,observation, and documentation. Furthermore, the hypothesis test was carried out using paired samplet-test. The results showed that there were differences in the results of the implementation of the ADIlearning model toward the students' argumentation skills with a significant value of 0.000 <0.05, then H0was rejected and H1 was accepted. The results of calculating the n-gain score using SPSS have an averagescore of 0.66 with moderate criteria. Student responses positively toward the implementation of the ADIlearning model with an average score of 84.15; The implementation of the ADI learning model obtained ascore of 88% with a good category. It can be concluded that the implementation of the Argument DrivenInquiry learning model can improve students' argumentation skills.